PRAANGGAPAN DALAM PAMFLET SOSIALISASI PELESTARIAN LINGKUNGAN DI KABUPATEN WAKATOBI - Karim, Karim; Maknun, Tadjuddin; Abbas, Asriani (JURNAL ILMU BUDAYA, 2019)
The presuppositions in the environmental conservation pamphlet in Wakatobi District are quite diverse. This study aims to explain the use of presupposition in the socialization pamphlet of environmental conservation in Wakatobi District. This research is a qualitative descriptive reseacrh that attempts to study presupposition phenomena with pragmatic approach. Type and data of this research is writing data sourced from pamphlet exixting in Wangi-wangi, Wakatobi District. Data were collected using observation method with recording and record technique. Data that has been obtained, classified and analyzed descriptively with qualitative approach. The result showed that, the use of presupposition in the environmental conservation pamphlet in Wakatobi District consisted of four types, namely existential presuppositions, factive presuppositions, structural presuppositions, and conterfactual presuppositions. The use of these presupposes there are differences in each pamphlet publisher, both goverment, non-govermental organizations, and pamphlet published collectively by goverment and non-govermental organizations. This difference is due to shared knowledge, participants, and the context of the situation.